Quantitative Characterization of Protein-Lipid Interactions by Free Energy Simulation Between Binary Bilayers - Park, Soohyung (J Chem Theory Comput, 2019)
Using a recently developed binary bilayer system (BBS) consisting of two patches of laterally contacting bilayers, umbrella sampling molecular dynamics (MD) simulations were performed for quantitative characterization of protein-lipid interactions. The BBS is composed of 1,2-dilauroyl-sn-glycero-3-phosphocholine (DLPC) and 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) with an embedded model membrane protein, a gramicidin A (gA) channel. The calculated free energy difference for the transfer of a gA channel from DLPC (hydrophobic thickness ≈ 21.5 Å) to DMPC (hydrophobic thickness ≈ 25.5 Å) bilayers, ΔG(DLPC→DMPC), is −2.2 ± 0.7 kcal/mol. This value appears at odds with the traditional view that the hydrophobic length of the gA channel is ~22 Å. To understand this discrepancy, we first note that recent MD simulations by different groups have shown that lipid bilayer thickness profiles in the vicinity of a gA channel differ qualitatively from the traditional deformation profile predicted from continuum elastic bilayer models. Our MD simulations at low and high gA:lipid molar ratios and different membrane compositions indicate that the gA channel’s effective hydrophobic length is ~26 Å. Using this effective hydrophobic length, ΔG(DLPC→DMPC) determined here is in excellent agreement with predictions based on continuum elastic models (−3.0 to −2.2 kcal/mol) where the bilayer deformation energy is approximated as a harmonic function of the mismatch between the channel’s effective hydrophobic length and the hydrophobic thickness of the bilayer. The free energy profile for gA in the BBS includes a barrier at the interface between the two bilayers which can be attributed to the line tension at the interface between two bilayers with different hydrophobic thicknesses. This observation implies that translation of a peptide between two different regions of a cell membrane (such as between the liquid ordered and disordered phases) may include effects of a barrier at the interface in addition to the relative free energies of the species far from the interface. The BBS allows for direct transfer free energy calculations between bilayers without a need of a reference medium, such as bulk water, and thus provides an efficient simulation protocol for the quantitative characterization of protein-lipid interactions at all-atom resolution.